Stronger and more failure-resistant with three-dimensional serrated bimetal interfaces. (March 2019) - Kong, X.F.; Beyerlein, I.J.; Liu, Z.R.; Yao, B.N.; Legut, D.; Germann, T.C.; Zhang, R.F.
Abstract: Low-energy structures of bimetal interfaces commonly occur in nature, yet higher energy forms, made by deviations in the interface plane, are also likely. While these variants may occur less frequently, they can still play an important role in the response of the material under deformation, by acting as preferential sites for defect formation and boundary motion. Here, using atomic-scale simulation and interface defect theory and considering two bimetal systems, Cu/Ag and Cu/Nb, we show that high-energy interfaces can achieve a local, low-energy state by forming atomic-scale serrations and that the predicted size and location of the serrations are consistent with experimental observation. For several distinct strain states, we reveal that interfaces with atomic-scale serrations bear both higher barriers for dislocation nucleation and higher resistances to interfacial shear compared to their planar interface variants. This desirable combination is not a characteristic of the more commonly studied low-energy interfaces, which typically possess a high nucleation barrier and low sliding resistance. We explain, through an analysis of the misfit dislocation structure, that the serrations alter the number of dislocations emitted, change the favorable slip systems, and alleviate the stress concentrations generated by misfit dislocations. An interface engineering strategy is then proposed for designing atomically serrated interfaces to improve mechanical strength and hinder localization and creep of metallic nanomaterials. Graphical abstract: Image 1